Beyond Lawrence: Metaprivacy and Punishment - Greene, Jamal (The Yale law journal, 2005)
Lawrence v. Texas remains, after three years of precedential life, an opinion in search of a principle. It is both libertarian – Randy Barnett has called it the constitutionalization of John Stuart Mill's On Liberty – and communitarian – William Eskridge has described it as the gay rights movement's Brown v. Board of Education. It is simultaneously broad, in its evocation of our deepest spiritual commitments, and narrow, in its self-conscious attempts to avoid condemning laws against same-sex marriage, prostitution, and bestiality. This Article reconciles these competing claims on Lawrence's jurisprudential legacy. In Part I, it defends the view that Lawrence constitutionalizes what I call metaprivacy : When societal consensus internalizes a breach of the historical legal divide between particular conduct and an associated status, punishment of that conduct cannot be based on moral approbation alone. The Article then, in Part II, harmonizes this view of Lawrence's legacy with pre-Lawrence constitutional privacy doctrine and theory. Finally, in Part III, the Article applies this understanding of Lawrence interdoctrinally, to capital sentencing. The Article suggests that all that separates the impermissible moral judgments made by a legislature in prohibiting sodomy from the permissible indeed, almost constitutionally required-moral judgments made during the sentencing phase of a capital trial is a preference for gays over other a priori criminals. Notwithstanding the obvious appeal of permitting such a preference, Lawrence provides no support for it